2010
DOI: 10.1016/j.toxicon.2010.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Human metabolites of brevetoxin PbTx-2: Identification and confirmation of structure

Abstract: Four metabolites were identified upon incubation of brevetoxin (PbTx-2) with human liver microsomes. Chemical transformation of PbTx-2 confirmed the structures of three known metabolites BTX-B5, PbTx-9 and 41, 43-dihydro-BTX-B5 and a previously unknown metabolite, 41, 43-dihydro-PbTx-2. These metabolites were also observed upon incubation of PbTx-2 with nine human recombinant cytochrome P450s (1A1, 1A2, 2C8, 2C9, 2C19, 2D6, 2E1, 3A4 and 3A5). Cytochrome P450 3A4 produced oxidized metabolites while other CYPs g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…To our knowledge, the metabolizing pathways of brevetoxins have not been described yet in these organisms. On the other hand, PbTx-2 metabolization associated to cytochrome P450 activity was confirmed in human, rat and fish CYPs [ 59 , 60 , 61 ]. Within metabolites described in these studies, some corresponded to metabolites identified in oyster tissues, e.g., PbTx-3 and PbTx-9 [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the metabolizing pathways of brevetoxins have not been described yet in these organisms. On the other hand, PbTx-2 metabolization associated to cytochrome P450 activity was confirmed in human, rat and fish CYPs [ 59 , 60 , 61 ]. Within metabolites described in these studies, some corresponded to metabolites identified in oyster tissues, e.g., PbTx-3 and PbTx-9 [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al [ 79 ] performed in vitro experiments incubating PbTx-2 with human liver microsomes. Three metabolites previously described, BTX-B5, PbTx-9, 41,43-dihydro-BTX-B5, and an additional unknown metabolite 41,43-dihydro-PbTx-2 were confirmed by LC–MS/MS ( Table 4 ).…”
Section: Mass Spectrometry To Identify Marine Biotoxins Metabolitesmentioning
confidence: 99%
“…The B-type toxins are considered more prevalent than the A-type toxins, with BTX-2 representing the most prevalent algal congener in K. brevis in both bloom and culture settings ( Twiner et al, 2007 ; Pierce et al, 2008 ; Errera et al, 2010 ; Lekan and Tomas, 2010 ). Aside from algal congeners, much of the present knowledge on BTX derivatives comes from studies with humans and rodents ( Poli et al, 2000 ; Wang et al, 2005 ; Radwan and Ramsdell, 2006 ; Abraham et al, 2008 ; Guo et al, 2010 ), as well as with shellfish ( Morohashi et al, 1995 , 1999 ; Murata et al, 1998 ; Poli et al, 2000 ; Plakas et al, 2002 , 2004 ; Ishida et al, 2004b ; Wang et al, 2004 ). These studies have shown that BTX-2 is rapidly absorbed, distributed, and eliminated primarily as metabolites, indicating that biotransformation plays a major role in the post-exposure processing and excretion of BTX ( Poli et al, 1990 ; Radwan et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…At least 70 BTX derivatives have been reported to date, although only about half of these have been structurally characterized ( ANSES, 2021 ; Hort et al, 2021 ). Phase I BTX-2 metabolites result mainly from cytochrome P450 monooxygenase (CYP)-dependent functionalization to several reduction and hydrolysis products (e.g., BTX-3, -9, the carboxylic acid derivative BTX-B5, as well as epoxide, diol, and A-ring hydrolysis products) ( Ishida et al, 2004a ; Radwan and Ramsdell, 2006 ; Guo et al, 2010 ). A variety of phase II metabolites have additionally been identified in mammals and shellfish, including cysteine and cysteine-sulfoxide conjugates arising from glutathione S-transferase (GST) pathways involving intermediate glutathione (GSH) metabolites ( Plakas et al, 2002 , 2004 ; Wang et al, 2004 ; Radwan and Ramsdell, 2006 ).…”
Section: Introductionmentioning
confidence: 99%